The Handbook of Humanistic Psychology: Theory, Research, and Practice 2015
DOI: 10.4135/9781483387864.n9
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Sustainable Myth of Self: An Existential Response to the Postmodern Condition

Abstract: The self has come under considerable attack in postmodern times. Amidst many deconstructions and reformulations of the self, various myths of self have lost their sustainability. This article reviews various theoretical perspectives on the self along with many postmodern challenges to the self. It is proposed that the self is a socially constructed entity which can be conceptualized from a variety of perspectives; however, not all myths of self are equal. In particular, premodern and modern myths of self are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 4 publications
0
19
0
1
Order By: Relevance
“…Humanistic and existential perspectives have tended to describe a self that is fluid, complex, and changing, yet stable (Hoffman, Stewart, Warren, & Meek, 2009). The participants in our study appeared to provide a clear embodiment of this complex and fluid yet stable identity.…”
Section: The Nature Of Spiritual Identity In This Studymentioning
confidence: 85%
“…Humanistic and existential perspectives have tended to describe a self that is fluid, complex, and changing, yet stable (Hoffman, Stewart, Warren, & Meek, 2009). The participants in our study appeared to provide a clear embodiment of this complex and fluid yet stable identity.…”
Section: The Nature Of Spiritual Identity In This Studymentioning
confidence: 85%
“…Consequently, Durrell can be described as an early postmodernist as he starts with deconstructing modernism. Hoffman andKurzenberger ISSN 1110-2721 found that "The early phase of postmodernism deconstructed modernism and the second phase began developing alternative epistemologies and methodologies" (Hoffman & Kurzenberger: 2008, p 83). Descartes looks upon man as a "thinking lobe".…”
Section: Issn 1110-2721mentioning
confidence: 99%
“…Like existentialism, postmodernism provides important philosophical theories, approaches, models, and techniques for understanding the human condition and how best to accentuate its attributes and confront its shortcomings (Hoffman, Stewart, Warren & Meek, 2009). Both approaches, however, may lack the level of pragmatic application some supervisors want and/or need to serve as independent alternatives to somewhat more established clinical and supervisory practices.…”
Section: Solution-focused Supervisionmentioning
confidence: 99%